Understanding immune-modulatory efficacy in vitro. (25th January 2022) - Khatua, Somanjana; Simal-Gandara, Jesus; Acharya, Krishnendu
Abstract: Boosting or suppressing our immune system represents an attractive adjunct in the treatment of infections including SARS-CoV-2, cancer, AIDS, malnutrition, age related problems and some inflammatory disorders. Thus, there has been a growing interest in exploring and developing novel drugs, natural or synthetic, that can manipulate our defence mechanism. Many of such studies, reported till date, have been designed to explore effect of the therapeutic on function of macrophages, being a key component in innate immune system. Indeed, RAW264.7, J774A.1, THP-1 and U937 cell lines act as ideal model systems for preliminary investigation and selection of dose for in vivo studies. Several bioassays have been standardized so far where many techniques require high throughput instruments, cost effective reagents and technical assistance that may hinder many scholars to perform a method demanding compilation of available protocols. In this review, we have taken an attempt for the first time to congregate commonly used in vitro immune-modulating techniques explaining their principles. The study detected that among about 40 different assays and more than 150 sets of primers, the methods of cell proliferation by MTT, phagocytosis by neutral red, NO detection by Griess reaction and estimation of expression of TLRs, COX-2, iNOS, TNF-α, IL-6 and IL-1β by PCR have been the most widely used to screen the therapeutics under investigation. Graphical abstract: Image 1 Highlights: Immunomodulation encompasses therapeutic interventions to suppress or enhance our body defense mechanism. Congregating in vitro techniques may help scholars to flourish in the field. Around 40 different assays have been described to investigate immune modulatory effect of a drug. More than 150 sets of primers related to the assays have been converged. Output of these assays may help to drive immunomodulatory science in vivo.